Epidemiology and outcomes of out-of-hospital cardiac arrest in Qatar: A nationwide observational study. (15th November 2016) - Irfan, Furqan B.; Bhutta, Zain Ali; Castren, Maaret; Straney, Lahn; Djarv, Therese; Tariq, Tooba; Thomas, Stephen Hodges; Alinier, Guillaume; Al Shaikh, Loua; Owen, Robert Campbell; Al Suwaidi, Jassim; Shuaib, Ashfaq; et al.
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) studies from the Middle East and Asian region are limited. This study describes the epidemiology, emergency health services, and outcomes of OHCA in Qatar. Methods: This was a prospective nationwide population-based observational study on OHCA patients in Qatar according to Utstein style guidelines, from June 2012 to May 2013. Data was collected from various sources; the national emergency medical service, 4 emergency departments, and 8 public hospitals. Results: The annual crude incidence of presumed cardiac OHCA attended by EMS was 23.5 per 100, 000. The age-sex standardized incidence was 87.8 per 100, 000 population. Of the 447 OHCA patients included in the final analysis, most were male (n = 360, 80.5%) with median age of 51 years (IQR = 39–66). Frequently observed nationalities were Qatari (n = 89, 19.9%), Indian (n = 74, 16.6%) and Nepalese (n = 52, 11.6%). Bystander cardiopulmonary resuscitation (CPR) was carried out in 92 (20.6%) OHCA patients. Survival rate was 8.1% (n = 36) and multivariable logistic regression indicated that initial shockable rhythm (OR 13.4, 95% CI 5.4–33.3, p = 0.001) was associated with higher odds of survival while male gender (OR 0.27, 95% CI 0.1–0.8, p = 0.01) and advanced cardiac life support (ACLS) (OR 0.15, 95% CI 0.04–0.5, p = 0.02) were associated with lower odds of survival. Conclusions: Standardized incidence and survival rates were comparable to Western countries. Although expatriates comprise more than 80% of the population, Qataris contributed 20% of the total cardiac arrests observed. There are significant opportunities to improve outcomes, including community-based CPR and defibrillation training.